Another look at research. (March 2016) - Oldfield, Chrissie
The traditional academic view of research is to derive new knowledge, generally involving studious inquiry and a search for new theories in order to contribute to an existing academic wealth of knowledge. This is alongside the primary objective of publishing peer reviewed articles in academic journals and the publication of relevant texts.